Hubungan Antara Lingkungan Pergaulan Dengan Perilaku Seks Bebas Pada Remaja Di Sman 1 Jemaja Tahun 2023 - Fairus Ardana; Wasis Pujiati; Zakiah Rahman; Safra Ria Kurniati (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Tanjungpinang, 2024)
Cases of sexual behavior are increasing and endangering adolescents and there is always an increase. Risky sexual behavior in adolescents if not handled properly can lead to unwanted pregnancies (KTD), trigger unsafe abortions, infanticide, STIs and HIV/AIDS, and even death. Seeing the impact above, it is necessary to know the factors that influence risky sexual behavior. The purpose of this study was to find out the relationship between the social environment and free sex behavior in adolescents at Jemaja 1 Public High School in 2023. The research design is Quantitative Descriptive Correlation with a cross sectional approach. The subjects of the study were 192 students in grades X - XI. Stratified Random Sampling sample collection technique. Respondents with a negative social environment were 136 (70.8%.) and respondents with a positive social environment were 56 (29.2%.) people. Respondents with bad sexual behavior were 127 (66.1%.) and respondents with good sexual behavior were 65 (33,9%.) people. Based on the p-value (0.020) <α 0.05 means that the social environment has a significant relationship to free sex behavior in adolescents. For adolescents, it is hoped that they can choose a place or social environment that is good with conditions and an atmosphere that can support and seek information about reproductive health and sex from trusted sources so that free sex behavior in adolescents does not occur between pre and post knowledge and behavior towards occupational health and safety education in Sri Tanjung village.